Self‐compressing object sequence for consistency maintenance in co‐editors. (21st April 2022) - Cai, Weiwei; He, Fazhi; Yang, Shangxu; Lv, Xiao; Cheng, Yuan
Abstract: Co‐editors are a class of human‐centered collaborative systems that allow multiple geographically dispersed people to freely and concurrently edit shared documents at the same time over networks. The most important building co‐editors technique is consistency maintenance. Even though OT (operational transformation) is a widely adopted consistency maintenance technique, researchers and practitioners have persistently explored alternative techniques to OT. One of the representative techniques is AST (Address Space Transformation), which replaces OT's transformation components with basic manipulation on an additional object sequence. However, the additional object sequence causes an unbounded metadata overhead problem. To solve the problem, this work proposes an optimized AST algorithm called ASTO, which is equipped with a specially designed self‐compressing object sequence. ASTO can automatically compress the object sequence and keep the metadata overhead under control. The effectiveness and feasibility of ASTO are verified by simulation experiments and a publicly accessible prototype system.